ANALISIS TINGKAT KESEHATAN BANK UMUM YANG TERDAFTAR PADA BURSA EFEK INDONESIA - Lase, Yarlenti; Banjarnahor, Haposan (LPPM Universitas Putera Batam, 2020)
This research is conducted to test impact of CAR (Capital Adequasi Ratio), NPL (Net Perfoming Loan), and LDR (Loan to Deposit Ratio) to ROA (Return On Assets). This research includes all General Bank assigned in Indonesian stockExchange (IDX) which provides financial statement from 2014 until 2018. All data obtained from bank yearly report from 2014 until 2018. Technical analysis which being used in this research is classical assumption test which includes normality, multicollinearity, autocorrelation, and heteroscedasticity test. Side test is to use multiple linear regression test using least square equation and hypothesis test using t-statistic to test partial regression coefficient and F-statistic simultant regression coefficient with significant level 5%. As a result of normality test shows that data is normally distributed. Based on the multicollinearity test, the autocorrelation test, and the heterokedasticity test no variables deviate from the classical assumptions. The results showed that the CAR variable had a significant effect on ROA, H1 was accepted, NPL did not have a significant effect on ROA, H2 was rejected and LDR had no significant effect on ROA, H3 was rejected.